2020
DOI: 10.3390/agriculture10120638
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Networks in the Prediction of Genetic Merit to Flowering Traits in Bean Cultivars

Abstract: Flowering is an important agronomic trait that presents non-additive gene action. Genome-enabled prediction allow incorporating molecular information into the prediction of individual genetic merit. Artificial neural networks (ANN) recognize patterns of data and represent an alternative as a universal approximation of complex functions. In a Genomic Selection (GS) context, the ANN allows automatically to capture complicated factors such as epistasis and dominance. The objectives of this study were to predict t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…While the crop model approach used derived phenotypes (estimated model parameters) to obtain QTL information, the mixed-effects model used QTL information obtained from genetic analysis of observed phenotypes. These results also demonstrated that the overall approach used in many crop models for computing rate of progress toward first flowering can be used in a statistical approach in which G, E, and Genomic selection [30] has been adopted by plant breeding programs world-wide because it is an affective methodology to predict the phenotype, including time-to-flowering [40,41] and in combination with artificial neural networks [42]. However, there are fundamental differences between genomic selection and QTL analysis.…”
Section: Discussionmentioning
confidence: 92%
“…While the crop model approach used derived phenotypes (estimated model parameters) to obtain QTL information, the mixed-effects model used QTL information obtained from genetic analysis of observed phenotypes. These results also demonstrated that the overall approach used in many crop models for computing rate of progress toward first flowering can be used in a statistical approach in which G, E, and Genomic selection [30] has been adopted by plant breeding programs world-wide because it is an affective methodology to predict the phenotype, including time-to-flowering [40,41] and in combination with artificial neural networks [42]. However, there are fundamental differences between genomic selection and QTL analysis.…”
Section: Discussionmentioning
confidence: 92%
“…Genomic selection [ 30 ] has been adopted by plant breeding programs world-wide because it is an affective methodology to predict the phenotype, including time-to-flowering [ 40 , 41 ] and in combination with artificial neural networks [ 42 ]. However, there are fundamental differences between genomic selection and QTL analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In GS, these functions automatically identify factors such as epistasis or dominance in genomic marker information. Moreover, it does not require any assumptions about the phenotypic distribution, and applying ANN to GS enables effective estimations of the effects of complex interactions ( Rosado et al., 2020 )…”
Section: Digitalizing Plant Breedingmentioning
confidence: 99%